IMPLEMENTASI MODEL COOPERATIVE LEARNING TEKNIK TALKING CHIPS DENGAN STANDAR KOMPETENSI â€œMEMAHAMI USAHA MANUSIA MENGENALIPERKEMBANGAN LINGKUNGANNYAâ€ UNTUK MENINGKATKAN KEPEDULIAN LINGKUNGAN DAN PRESTASI BELAJAR IPS SISWA KELAS VIIA SMP NEGERI 1 MONDOKAN SRAGEN - Handayani, Sri (HISTORIKA, 2015)
The purpose ofthis study was to: Deskrepsi analysis of Implementation Cooperative Model Technique Leaning Talking Chip swith Competency Standards Recognize Human Understanding Business Development Environment can increase environmental awareness and social studiesachievementseven A (VIIA) grade social studies students of Junior High School State One Mondokan Sragen.This study uses a Class Action Research. The population Seven A (VIIA) grade students of Junior High School State One Mondokan, Sragen academic year 2014/2015. This study is designed into three cycles, each cycle consisting of four phases, namely: Planning, Implementation/Provision action, Observation, and Reflection. For data on environmental awareness and learning achievement, using test method, observation, interviews and documentation of data while affective and psychomotor using observation sheet. Mechanical examination of the validity of data used triangulation techniques of observation and perseverance. Triangulation is used in this research is triangulation method, which compares the research findings obtained from multiple data collection techniques.Research results obtained from the observation of the students at the time of execution of the model Cooperative Learning Techniques Talking Chips with Competency Standards Recognize Human Understanding Business Development Environment and the results of the attitude there is an increasing environmental concern of 19% pre-cycle, the first cycle reaches 31%, the second cycle reaches 59, 4% and the third cycle has reached 88%, it means that already exceeds the target of â‰¥ 85% of students in one class have environmental concerns. While the results of the achievement of mastery in the classical experience a significant increase from 47% pre-cycle, the first cycle increased to 60%, the second cycle reaches 72% whereas the third cycle reaches 97%. This means classically been exceeded because the target of about â‰¥85% of students have a value equal to or more than Minimal Completeness Criteria (â‰¥70%). Seeing the results of observations that have been made above, it can be said that this method of learning with learning models Cooperative Learning Techniques Talking Chips, it can be said to be successful because of the attitude of environmental concerns and student achievement in understanding the human effort to identify developmental environment increased significantly. The results showed that the application of cooperative learning models Talking Chips technique has many advantages, students can be encouraged to learn while playing, making the atmosphere in the classroom more fun, cooperation for mutual aid in understanding the subject matter and successfully led students to value the opinions of other students. For teachers themselves can also improve the quality and the role of teachers in delivering lessons to students. By applying the model coopertive Learning Techniques Talking Chips in delivering a lesson, it will be able to increase the awareness, enthusiasm and activeness of the students, so that they can understand the subject matter accepted that learning achievement will be better and able to practice in daily life.The results showed that: Model Cooperative Learning Techniques Talking Chips with Competency Standards Recognize Human Understanding Business Development Environment can be applied/implemented so that increase environmental awareness and social studies achievement in Seven A (VIIA) grade students of Junior High School State One Mondokan Sragen.Â